Workshop-based learning and networking: a scalable model for research capacity strengthening in low- and middle-income countries. Issue 1 (31st December 2022) - Perier, Celine; Nasinghe, Emmanuel; Charles, Isabelle; Ssetaba, Leoson Junior; Ahyong, Vida; Bangs, Derek; Beatty, P. Robert; Czudnochowski, Nadine; Diallo, Amy; Dugan, Eli; Fabius, Jacqueline M.; Fong Baker, Hildy; et al.
ABSTRACT: Science education and research have the potential to drive profound change in low- and middle-income countries (LMICs) through encouraging innovation, attracting industry, and creating job opportunities. However, in LMICs, research capacity is often limited, and acquisition of funding and access to state-of-the-art technologies is challenging. The Alliance for Global Health and Science (the Alliance) was founded as a partnership between the University of California, Berkeley (USA) and Makerere University (Uganda), with the goal of strengthening Makerere University's capacity for bioscience research. The flagship program of the Alliance partnership is the MU/UCB Biosciences Training Program, an in-country, hands-on workshop model that trains a large number of students from Makerere University in infectious disease and molecular biology research. This approach nucleates training of larger and more diverse groups of students, development of mentoring and bi-directional research partnerships, and support of the local economy. Here, we describe the project, its conception, implementation, challenges, and outcomes of bioscience research workshops. We aim to provide a blueprint for workshop implementation, and create a valuable resource for bioscience research capacity strengthening in LMICs.